Systematic Literature Review: Validitas Konstruk Skala Psychological Well-Being Ryff - Aditia Kharisma Meliala; Ahman Ahman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The study of psychological well-being has received increasing attention in the last decade, especially integrated into the field of positive psychology. One of the difficulties in grasping a deep understanding of the concept of psychological well-being is due to the wide variety of concepts used interchangeably in the literature. Ryff (1989), undertook the difficult task of distilling the theories of the original psychological well-being model. Ryff's model integrates the theoretical components of Abraham Maslow's concept of self-actualisation, Rogers' view of the fully functioning person, Allport's individual formulation of the concept of maturity, Erikson's psychosocial stages model, Buhler's basic life tendencies, Neugarten's personality change, Jahoda's positive criteria of mental health. Ryff's theory includes six basic dimensions of psychological well-being, namely 1) Autonomy, 2) Environmental control, 3) Personal growth, 4) Positive relationships with others, 5) Life purpose, 6) Self-acceptance. The procedure used for the systematic review in this study was designed based on the PRISMA (Protocol Review Systematic and Meta-Analysis) statement. This article suggests that future researchers in an effort to conduct construct testing on Ryff's psychological well-being scale, it is recommended to test the validity of content, convergent, and criteria.